SOCIAL WORK MANAGEMENT AND SOCIAL ENTREPRENEURSHIP WITHIN THE SYSTEM OF SOCIAL INNOVATION: A SOCIO-PSYCHOLOGICAL PERSPECTIVE - Haba, Iryna; Palamarchuk, Olha (Personality and environmental issues, 2026)
The article examines the interrelation between social work management and social entrepreneurship within the system of social innovation from a socio-psychological perspective. The relevance of the topic is determined by the increasing complexity of social challenges, the need to renew models of social service organization, the growing role of cross-sectoral interaction, and the search for sustainable mechanisms for supporting vulnerable population groups in the context of Ukraine’s wartime and post-war development. It is substantiated that contemporary social work management encompasses not only the organization and control of service delivery, but also planning, coordination, needs assessment, case management, partnership development, resource provision, and outcome monitoring. It is demonstrated that social entrepreneurship emerges as one of the organizational forms of implementing social innovation, capable of combining a social mission, an entrepreneurial approach, institutional flexibility, and social impact. The main dimensions of the interrelation between social work management and social entrepreneurship are identified as resource-related, organizational and managerial, social integration, institutional, and innovative. It is emphasized that, from a socio-psychological perspective, social entrepreneurship contributes not only to the diversification of resources and the development of project-oriented management, but also to the expansion of opportunities for social integration, the strengthening of individual agency, the activation of participation, and the formation of a more inclusive social environment. Prospects for further research are associated with the development of models for integrating social entrepreneurship into the system of social services at the level of territorial communities, the identification of criteria for assessing its social impact, the analysis of managerial competencies required of social work professionals,